Modular and rapid testing of SOCs with unwrapped logic blocks. - Qiang Xu (IEEE Transactions on VLSI systems)
Extensive research has been carried out for test planning of core-based system-on-a-chip devices. Most of the prior work assumes that all of the embedded cores are wrapped for test purpose. However, some designs may contain user-defined logic or cores that cannot be wrapped due to area constraints or timing violations. This paper discusses how these unwrapped logic blocks can be tested rapidly by adapting the TestRail architecture, which uses only the test control mechanism and the test instructions available through the IEEE 1500 standard for embedded core test. A new test scheduling algorithm, which facilitates a concurrent test of both unwrapped logic blocks and IEEE 1500-wrapped cores, is proposed, and experiments show that it outperforms a previous approach when the available number of tester channels and/or the number of unwrapped logic blocks are small.